PENGARUH KOMITMEN ORGANISASI, IKLIM KERJA DAN PENGEMBANGAN KARIR TERHADAP SEMANGAT KERJA KARYAWAN PADA SEKOLAH TINGGI X JAKARTA - EZPERANZA, REZA; PUJIANTO, SURAHMAN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This studies are intended to determine the effect of Organizational Commitment, Work Climate and Career Development on Employee Morale at Sekolah Tinggi X Jakarta. The population of this study were all employees at Sekolah Tinggi X Jakarta. Researchers chose 60 respondents as a sample from this study, using saturated samples and data collected using questionnaires. This study use a statistical methods, with the SPSS Version 25 as a test tool. The results of this study indicate that the Work Climate and Career Development have an influence on Work Spirit. However, Organizational Commitment has no influence on the Employees' Morale at Sekolah Tinggi X Jakarta.